Predictive Shear Strength Models for Tropical Lateritic Soils - Oluwapelumi O. Ojuri (Journal of Engineering)
This research focused on the indirect determination of soil shear strength using basic soil properties for a lateritic soil area. Samples were collected from six different locations in the Federal University of Technology Akure, Ondo State, Nigeria. These lateritic soils fall within the A-2, A-6, and A-7 groups in the AASHTO classification system. Exploratory analysis of the six independent variables was performed using the statistical analysis of principal components. The stepwise multiple regression was used to establish the best predictive models for the California bearing ratio (CBR) and undrained shear strength (). A remarkable significant model for undrained shear strength [] with ( = 229.476, , Adjusted = 0.989, Std. Error = 7.5638) emerged. This model accounts for 99.4% of variation in the dependent variable. For the included predictor variables beta = 0.722, and beta = −0.417, for MDD and GI, respectively, where other variables are excluded from the model. This makes a quick evaluation of the shear strength of lateritic soils by using their maximum dry density and group index values possible.